Role of information for rural development in ACP countries : review and perspectives: proceedings of an international seminar Montpelier, France... 1995 (CTA WageningenNL, 1995)
Focuses on the evolving information needs of ACP countries over the next 10 years, and on necessary changes in the supply of information, its production and dissemination. Presents strategic options for adapting CTA programmes towards rural information.
DC